LITERATURE STUDY: E-MODULES BASED ON CONTEXTUAL TEACHING AND LEARNING (CTL) AS THE MAIN SOLUTION TO IMPROVING CRITICAL THINKING ABILITY - Muhammad Fajar Marsuki; Nassa Amrilizia; Habiddin Habiddin (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2021)
This study aims to examine the literature on the need for Contextual Teaching and Learning (CTL)-based modules as the main solution to improving the critical thinking skills of grade 7 students. The results of research and international surveys such as PISA show that the critical thinking ability profile of Indonesian students is inadequate. This phenomenon is caused by teachers still focusing on learning outcomes that show indicators of student learning mastery, while students are not allowed to explore knowledge and relate science concepts in everyday life. This has an impact on the concepts taught are still less meaningful and rote, and student’s understanding of concepts is still low causing students' process skills in critical thinking cannot be exploited. The right learning media needs to be chosen by an educator to improve critical thinking skills, namely Contextual Teaching and Learning (CTL) based modules. This research is qualitative. The instruments used in this research are interview tests for teachers and an analysis of the needs of students at Junior High School 8 Malang, Indonesia. The method used is a literature review, interviews, and observing the teachers and students in learning science at Junior High School 8 Malang. Based on the literature review, an ideal solution was obtained to solve the problem, namely an update to a more ideal learning process, namely learning media in the form of e-modules based on Contextual Teaching and Learning (CTL) that can link the learning materials studied in schools with facts that students encounter in everyday life.